“Seminal testosterone”, rising viewpoint of local spermatogenesis in nonobstructive azoospermia: One center long-term bidirectional cohort study - Liu, Huang; Zheng, Houbin; Li, Yuehua; Tang, Yuqian; Peng, Hongbo; Li, Qianyi; Zhuang, Jiaming; Zhou, Yingyi; Zhou, Yu; Tu, Xiang’an; Zhang, Xinzong (Frontiers in Endocrinology, 2022)
Objective: In order to find a more accurate method, the seminal reproductive hormones were studied. Methods: Bidirectional cohort study was performed in the study. 126 infertile men from 2018 to 2019 were retrospectively analyzed. They were divided into non-obstructive azoospermia (NOA), oligozoospermia (OLZ) and normal group (NOR). Prospective study was conducted on patients in NOA and OLZ group for 2 years. Microscopic testicular sperm extraction was performed for NOA patients, of whom were divided into focal spermatogenesis group (FS) and idiopathic azoospermia group (IA). Drugs treatment was for OLZ patients, of whom were divided into valid group (VA) and invalid group (IN). The differences of sperm parameters and reproductive hormones were compared. ANOSIM analysis was used between and within groups. Pearson correlation analysis, CO inertia analysis and proctor's analysis were for relationships. ROC curve for the specificity and sensitivity. Time series analysis was for the trends between hormones and time. Results: the b-FSH, b-LH, s-T and ∆T in NOA group were significantly higher than those in OLZ and NOR group. However, the s-FSH, s-E2, s-P, ∆FSH, ∆LH, ∆P and ∆E2 were lower. 31 NOA patients underwent the MTSE, of which, 12 obtained sperm (FS) and 19 had no (IA), s-FSH and s-E2 of FS group were higher than IA group. 26 OLZ patients completed 30 days’ treatment, of which 11 improved sperm count (VA) and 15 had no (IN), the ∆T of VA group was higher than IN group. Follow-up for 2-years, 18 patients’ results showed b-FSH, b-LH and s-T were different over time with delaying of 19, 3 and -19 days. SC closely related to pH, seminal hormones, b-FSH, b-LH, ∆FSH, ∆LH, ∆P, ∆E2 and ∆T. There were complex common trends and relationships between different kinds of hormones. seminal hormones, b-FSH and b-LH were useful to judge spermatogenesis, of which, s-T, b-FSH and b-LH were more sensitive. If s-T, b-FSH and b-LH respectively reached 64.4, 9.4 and 4.7, their prediction achieved the strongest. Conclusion: Seminal testosterone is sensitive to judge local spermatogenesis in non-obstructive azoospermia patients, which may achieve as the rising viewpoint of local spermatogenesis in non-obstructive azoospermia.